Economic and Socio-Cultural Impacts of the World Nomad Games - Maksudunov, Azamat (Economy of Regions, 2020)
The World Nomad Games (WNG) is a new form of large-scale events in the world. Thus, little empirical research is focused on understanding perceived impacts of the WNG and behavioural tendencies of the host community. The research aims to reveal the perceptions of the local people regarding the possible impacts from hosting the World Nomad Games in two different localities of the Kyrgyz Republic. The impacts of the WNG were measured using a survey conducted among local residents based on face-to-face interviews. The study examines data collected from two localities in the Kyrgyz Republic: 384 surveys from Bishkek, the capital city of Kyrgyzstan (first group), and 286 interviews from Issyk-Kul region where the WNG were held (second group). According to the results, the local residents have positive perceptions about the impacts of the WNG and support hosting this event in Kyrgyzstan. The residents believe that the WNG result in the eco- nomic development, revitalization of the tourism sector, increased infrastructure investments. Moreover, the positive impacts include preservation and development of local cultures, host country promotion and enhancement of the country’s image. However, hosting the WNG created different impacts in different localities. In this context, for the Bishkek sample, the economic dimension was the most important factor, while for the Issyk-Kul sample the cultural dimension came to the forefront.